2015
DOI: 10.14400/jdc.2015.13.10.445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Pain and Social support on Depression and Suicide in the Elderly

Abstract: This research is aged 65 or older with chronic pain and social support, are subject to the elderly wanted to know the effect on depression and suicide intention. This research was done through targeting elderly with chronic pain who use welfare center. The data collection period from April 20 in 2014, implemented by May 20. finally 178 kinds of types of data were analyzed. The collected data is Person's correlation coefficient, and multiple regression analysis by using SPSS 18.0, t-test, ANOVA. In this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In addition, social support had a negative (-) direct effect on symptoms and functional disability, and a positive (+) direct effect on health perception. Our study found that social support, an environmental characteristic, affects symptoms such as pain, physical function, and depression [6,35]. This is consistent with the results of previous studies [13,18] which reported that social support indirectly affects health-related quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, social support had a negative (-) direct effect on symptoms and functional disability, and a positive (+) direct effect on health perception. Our study found that social support, an environmental characteristic, affects symptoms such as pain, physical function, and depression [6,35]. This is consistent with the results of previous studies [13,18] which reported that social support indirectly affects health-related quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it can cause depression and lower the quality of life [4,5,6,7]. The hospitalized cancer patients have a hard time to express their pain so it becomes an obstacle in managing the cancer pain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, about 70% of the haenyeo population have been found to be analgesic abusers, which highlights the serious health risks confronting haenyeos (Choi et al, 2008;Koh, Cho, Yang, & Kim, 2015). Furthermore, depression is a common health problem for elderly people in a Jeju Hanmaum Hospital, South Korea b Department of Nursing, College of Nursing, Jeju National University, South Korea general; the more chronic diseases they have, the more depressed they are (Jeong & Kim, 2013;Lee & Yang, 2010;Lim, 2014), and the higher the pain that they experience, the more depressed they become (Lee & Moon, 2015). Hence, aging haenyeos are likely to experience a vicious cycle of chronic diseases, depression, and pain.…”
Section: Review Of Literaturementioning
confidence: 99%